DNA methylation at modifier genes of lung disease severity is altered in cystic fibrosis. Issue 1 (December 2017) - Magalhães, Milena; Rivals, Isabelle; Claustres, Mireille; Varilh, Jessica; Thomasset, Mélodie; Bergougnoux, Anne; Mely, Laurent; Leroy, Sylvie; Corvol, Harriet; Guillot, Loïc; Murris, Marlène; Beyne, Emmanuelle; et al.
Abstract Background Lung disease progression is variable among cystic fibrosis (CF) patients and depends on DNA mutations in theCFTR gene, polymorphic variations in disease modifier genes, and environmental exposure. The contribution of genetic factors has been extensively investigated, whereas the mechanism whereby environmental factors modulate the lung disease is unknown. In this project, we hypothesized that (i) reiterative stress alters the epigenome in CF-affected tissues and (ii) DNA methylation variations at disease modifier genes modulate the lung function in CF patients. Results We profiled DNA methylation atCFTR, the disease-causing gene, and at 13 lung modifier genes in nasal epithelial cells and whole blood samples from 48 CF patients and 24 healthy controls. CF patients homozygous for the p.Phe508del mutation and ≥18-year-old were stratified according to the lung disease severity. DNA methylation was measured by bisulfite and next-generation sequencing. The DNA methylation profile allowed us to correctly classify 75% of the subjects, thus providing a CF-specific molecular signature. Moreover, in CF patients, DNA methylation at specific genes was highly correlated in the same tissue sample. We suggest that gene methylation in CF cells may be co-regulated by disease-specifictrans -factors. Three genes were differentially methylated in CF patients compared with controls and/or in groups of pulmonary severity:HMOX1 andGSTM3 in nasal epithelial samples;HMOX1 andEDNRA in blood samples. The association between pulmonary severity and DNA methylation atEDNRA was confirmed in blood samples from an independent set of CF patients. Also, lower DNA methylation levels atGSTM3 were associated with theGSTM3*B allele, a polymorphic 3-bp deletion that has a protective effect in cystic fibrosis. Conclusions DNA methylation levels are altered in nasal epithelial and blood cell samples from CF patients. Analysis ofCFTR and 13 lung disease modifier genes shows DNA methylation changes of small magnitude: some of them are a consequence of the disease; other changes may result in small expression variations that collectively modulate the lung disease severity.